Structure Learning with Nonparametric Decomposable Models - Schwaighofer, Anton; Dejori, Mathäus; Tresp, Volker; Stetter, Martin (Artificial Neural Networks - ICANN 2007, 2007)
We present a novel approach to structure learning for graphical models. By using nonparametric estimates to model clique densities in decomposable models, both discrete and continuous distributions can be handled in a unified framework. Also, consistency of the underlying probabilistic model is guaranteed. Model selection is based on predictive assessment, with efficient algorithms that allow fast greedy forward and backward selection within the class of decomposable models. We show the validity of this structure learning approach on toy data, and on two large sets of gene expression data.